Dampak Perceraian terhadap Pendidikan Anak: Studi Kasus Desa Ciherang Pondok, Caringin Bogor - Talitha Raissa Zhafira; Sutisna Sutisna; Yono Yono (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Divorce is the severance of the relationship between husband and wife, caused by failure husband or wife in carrying out all the bonding roles of each. This research is based on turn to the consenquences of parental divorce on children’s education. The purpose of the study is to find out how the impact of divorce in law Islam, to find out how the impact of divorce on children’s education in the village Ciherang Pondok, to find out how to overcome the impact of divorce on children’s education in Ciherang Pondok Village. The research method used is research qualitative method with descriptive method, while the data collection techniques used are observation,interview and documentation. The data analysis procedures used in this research is a data analysis of the Miles and Huberman Model, namely : data collection (data collection), data reduction, display (data presentation), levers (data collection). From the result of the study show that : in Islamic teachings, divorce is indeed not prohibited and it is allowed, but it is hated by Allah SWT, the education of the child of the victim’s child divorce has a huge impact on children’s education, attitudes and behavior as well as learning achievement declining, one of the efforts to overcome the impact of divorce on children’s education is inseparable from the role of parents, teachers,and the people around them. Keywords: Impact of divorce, children, education,